PEMANFAATAN MEDIA POWERPOINT UNTUK MENINGKATKAN MINAT DAN KREATIVITAS SISWA DALAM PEMBELAJARAN IPAS KELAS IV SD NEGERI UJONG FATIHAH KECAMATANKUALA KABUPATEN NAGAN RAYA - Muttaqin; Rita Oktavia; Fitri Fadhilla (Jurnal Binagogik, 2026)
The role of instructional media is crucial in supporting the success of the teaching-learning process, especially in Integrated Science and Social Studies (IPAS) which requires contextual and multi-sensory approaches. However, fieldwork still finds constraints such as a lack of student enthusiasm and minimal media variation, leading to low interest and creativity. This study aims to describe the utilization of PowerPoint media in IPAS learning for fourth grade students at SD Negeri Ujong Fatihah and to analyze its effect on increasing student interest and creativity. This research uses a descriptive qualitative approach. The research subjects consisted of the IPAS teacher and fourth-grade students, with data collection techniques including participatory observation, in-depth interviews, documentation, and questionnaires. The results show that PowerPoint media was optimally utilized by the teacher in structuring and presenting the material sequentially, attractively, and in accordance with learning objectives. The use of PowerPoint made the learning process more interactive through varied visual and audio displays. This positively impacted the increase in student interest in following the learning, as well as encouraging the development of student creativity. Thus, the utilization of PowerPoint media is proven effective in enhancing the quality of IPAS learning in fourth grade at SD Negeri Ujong Fatihah.